A couple stress model in non-polynomial framework to examine structural responses of laminated composite micro-plates: An analytical solution. (1st April 2021) - Joshan, Y.S.; Sharma, L.K.; Grover, Neeraj; Godara, R.K.
Highlights: The laminated composite micro-plates are modeled in the framework of refined couple stress theory using various non-polynomial shear deformation theories (NPSDTs). The size effects are considered by employing the scale effects in the virtual strain energy under the framework of refined couple stress theory. The non-dimensional results are obtained for bending, buckling and free vibration responses of cross-ply laminated composite micro-plates in terms of transverse deflection, stresses, buckling load and fundamental frequency. The effects of various parameters such as lamination sequence, scale parameter, spanthickness ratio, anisotropy ratio, etc. are examined. Abstract: In the present article, the couple stress models in the non-polynomial framework are developed and employed to examine the structural response characteristics of composite micro-plates. The length scale effects in the micro-laminates are considered using the couple stress theory. The trigonometric, inverse-trigonometric, hyperbolic, inverse-hyperbolic and exponential shear shape functions are considered to model transverse shear deformation effects in micro-plates. The Hamilton principle is employed to formulate the governing equations assuming linear structural kinematics. The governing equations are solved for simply supported micro-plates using the Navier solution for the prediction of analytical results. The structural responses of the composite micro-plates are examined for bending, free vibration, and buckling responses. The nondimensionalized deflection, stresses, frequencies, and axial buckling loads are evaluated using the present methodology. The higher buckling modes and free vibration modes are also obtained. The response characteristics due to five plate theories are compared and the applicability of the considered transverse shear deformation theories to model and analyze composite micro-plates is assessed. The effects of various parameters on the structural responses of micro-laminates are examined.